Influence of secondary compound complementarity and species diversity on consumption of Mediterranean shrubs by sheep - Rogosic, Jozo; Estell, Richard E; Skobic, Dragan; Stanic, Svjetlana (Applied Animal Behaviour Science, 2007)
Generalist herbivores foraging in chemically diverse grazing ecosystems like the Mediterranean maquis increase intake on mixed diets, suggesting they are more able to meet nutritional needs and avoid toxicosis. Thus, our objectives were to determine how shrub species diversity and complementary interactions between tannins and saponins inﬂuence intake of Mediterranean shrubs by sheep. We conducted four experiments (10 days each) comparing intake of mixtures of Mediterranean shrubs varying in number of species and/or principal class of secondary compound (tannins or saponins) by sheep (n = 12). Sheep consumed more total foliage (P < 0.01) when offered a high-tannin shrub (Pistacia lentiscus; Exp. 1), two high-tannin shrubs (P. lentiscus and Arbutus unedo; Exp. 2), or three high-tannin shrubs (P. lentiscus, A. unedo, and Quercus ilex; Exp. 3) when fed in conjunction with a high-saponin shrub (Hedera helix) than with an equal number of high-tannin shrubs (20.9 g/kg BW versus 16.3 g/kg BW; 28.8 g/kg BW versus 20.8 g/kg BW; and 35.3 g/kg BW versus 26.9 g/kg BW). Likewise, sheep ate more foliage (P < 0.01) of each additional individual shrub (P. lentiscus, A. unedo, and Q. ilex) in the mixture when fed with H. helix than with an equal number of high-tannin shrubs (8.2 g/kg BW versus 5.0 g/kg BW; 13.3 g/kg BW versus 10.7 g/kg BW; and 7.6 g/kg BW versus 5.2 g/kg BW; Exps. 1–3, respectively), suggesting a complementary interaction between tannins and saponins may have occurred. Sheep also appeared to increase total shrub intake as number of shrub species on offer increased, regardless of number of classes of compounds present. Our ﬁndings suggest that secondary compounds in Mediterranean shrubs (tannins and saponins) are complementary. Species diversity also plays an important role in diet selection, as plant species with different types and amounts of nutrients and phytotoxins may affect forage intake and animal production. This knowledge will help livestock producers to capitalize on phytochemical interactions to enhance intake, optimize forage utilization, and ultimately improve performance of browsing ruminant herbivores
Keywords: Biodiversity; Complementarity; Mediterranean maquis; Saponins; Secondary compounds; Sheep; Shrubs; Tannins

Influence of secondary compound complementarity and species diversity on consumption of Mediterranean shrubs by sheep - Rogosic, Jozo; Estell, Richard E.; Skobic, Dragan; Stanic, Svjetlana (Applied Animal Behaviour Science, 2007)
Generalist herbivores foraging in chemically diverse grazing ecosystems like the Mediterranean maquis increase intake on mixed diets, suggesting they are more able to meet nutritional needs and avoid toxicosis. Thus, our objectives were to determine how shrub species diversity and complementary interactions between tannins and saponins inﬂuence intake of Mediterranean shrubs by sheep. We conducted four experiments (10 days each) comparing intake of mixtures of Mediterranean shrubs varying in number of species and/or principal class of secondary compound (tannins or saponins) by sheep (n = 12). Sheep consumed more total foliage (P < 0.01) when offered a high-tannin shrub (Pistacia lentiscus; Exp. 1), two high-tannin shrubs (P. lentiscus and Arbutus unedo; Exp. 2), or three high-tannin shrubs (P. lentiscus, A. unedo, and Quercus ilex; Exp. 3) when fed in conjunction with a high-saponin shrub (Hedera helix) than with an equal number of high-tannin shrubs (20.9 g/kg BW versus 16.3 g/kg BW; 28.8 g/kg BW versus 20.8 g/kg BW; and 35.3 g/kg BW versus 26.9 g/kg BW). Likewise, sheep ate more foliage (P < 0.01) of each additional individual shrub (P. lentiscus, A. unedo, and Q. ilex) in the mixture when fed with H. helix than with an equal number of high-tannin shrubs (8.2 g/kg BW versus 5.0 g/kg BW; 13.3 g/kg BW versus 10.7 g/kg BW; and 7.6 g/kg BW versus 5.2 g/kg BW; Exps. 1–3, respectively), suggesting a complementary interaction between tannins and saponins may have occurred. Sheep also appeared to increase total shrub intake as number of shrub species on offer increased, regardless of number of classes of compounds present. Our ﬁndings suggest that secondary compounds in Mediterranean shrubs (tannins and saponins) are complementary. Species diversity also plays an important role in diet selection, as plant species with different types and amounts of nutrients and phytotoxins may affect forage intake and animal production. This knowledge will help livestock producers to capitalize on phytochemical interactions to enhance intake, optimize forage utilization, and ultimately improve performance of browsing ruminant herbivores
Keywords: Biodiversity; Complementarity; Mediterranean maquis; Saponins; Secondary compounds; Sheep; Shrubs; Tannins

Role of species diversity and secondary compound complementarity on diet selection of Mediterranean shrubs by goats. - Rogosic, Jozo; Estell, Richard E; Skobic, Dragan; Martinovic, Anita; Maric, Stanislava (Journal of chemical ecology, 2006)
Goats foraging on Mediterranean shrubs containing secondary compounds (toxins) may consume a variety of shrubs that contain different phytotoxins, thereby increasing shrub intake and avoiding toxicosis. We conducted eight experiments to examine whether goats offered different mixtures of shrubs containing different phytotoxins (tannins and saponins) would consume more shrub biomass than goats offered one shrub a single phytotoxin (tannin or saponin). In the first three experiments, goats fed a mixture of three tannin-rich shrubs (Quercus ilex, Arbutus unedo, and Pistacia lentiscus) ate more foliage than goats offered only one shrub (23.2 vs. 10.7 g/kg BW; 25.2 vs. 13.4 g/kg BW, and 27.9 vs. 7.9 g/kg BW), regardless of tannin concentration in individual shrub species. Goats also consumed more foliage when offered the same three tannin-rich shrubs than when offered the saponin-rich shrub Hedera helix (25.4 vs. 8.0 g/kg BW). However, goats offered a mixture of the same three tannin-rich shrubs consumed less foliage than goats offered a mixture of two shrubs containing tannins and saponins: Quercus and Hedera (21.6 vs. 27.1 g/kg BW), Arbutus and Hedera (21.8 vs. 27.1 g/kg BW), and Pistacia and Hedera (19.7 vs. 22.0 g/kg BW). Comparison of intake of shrubs containing only tannins or saponins to intake of shrubs containing both tannins and saponins indicated that goats consumed more total biomass when fed with shrubs with both classes of compounds than with either tannins or saponins alone. Our results suggest that goats can increase intake of Mediterranean shrubs high in secondary compounds by selecting those with different classes of phytotoxins. Simultaneous ingestion of shrubs containing tannins and saponins may promote chemical interactions that inhibit toxic effects of these phytotoxins in the intestinal tract. In addition to complementary interactions between tannins and saponins, biological diversity within Mediterranean maquis vegetation also plays a positive role in increasing shrub intake by goats.
Keywords: Biodiversity; Goats; Maquis; Mediterranean shrubs; Saponins; Secondary compounds; Tannins

Role of species diversity and secondary compound complementarity on diet selection of Mediterranean shrubs by goats. - Rogosic, Jozo; Estell, Richard E.; Skobic, Dragan; Martinovic, Anita; Maric, Stanislava (Journal of chemical ecology, 2006)
Goats foraging on Mediterranean shrubs containing secondary compounds (toxins) may consume a variety of shrubs that contain different phytotoxins, thereby increasing shrub intake and avoiding toxicosis. We conducted eight experiments to examine whether goats offered different mixtures of shrubs containing different phytotoxins (tannins and saponins) would consume more shrub biomass than goats offered one shrub a single phytotoxin (tannin or saponin). In the first three experiments, goats fed a mixture of three tannin-rich shrubs (Quercus ilex, Arbutus unedo, and Pistacia lentiscus) ate more foliage than goats offered only one shrub (23.2 vs. 10.7 g/kg BW; 25.2 vs. 13.4 g/kg BW, and 27.9 vs. 7.9 g/kg BW), regardless of tannin concentration in individual shrub species. Goats also consumed more foliage when offered the same three tannin-rich shrubs than when offered the saponin-rich shrub Hedera helix (25.4 vs. 8.0 g/kg BW). However, goats offered a mixture of the same three tannin-rich shrubs consumed less foliage than goats offered a mixture of two shrubs containing tannins and saponins: Quercus and Hedera (21.6 vs. 27.1 g/kg BW), Arbutus and Hedera (21.8 vs. 27.1 g/kg BW), and Pistacia and Hedera (19.7 vs. 22.0 g/kg BW). Comparison of intake of shrubs containing only tannins or saponins to intake of shrubs containing both tannins and saponins indicated that goats consumed more total biomass when fed with shrubs with both classes of compounds than with either tannins or saponins alone. Our results suggest that goats can increase intake of Mediterranean shrubs high in secondary compounds by selecting those with different classes of phytotoxins. Simultaneous ingestion of shrubs containing tannins and saponins may promote chemical interactions that inhibit toxic effects of these phytotoxins in the intestinal tract. In addition to complementary interactions between tannins and saponins, biological diversity within Mediterranean maquis vegetation also plays a positive role in increasing shrub intake by goats.
The following values have no corresponding Zotero field: accession-num: 16770718
Keywords: Biodiversity; Goats; Maquis; Mediterranean shrubs; Saponins; Secondary compounds; Tannins

Assessment of the digestibility of some Mediterranean shrubs by in vitro techniques - Ammar, H; López, S; González, J S (Animal Feed Science and Technology, 2005)
The nutritive value of some Mediterranean browse species collected in Tunisia was studied on the basis of their chemical composition, in vitro digestibility and fermentation kinetics (gas production technique). The browse species evaluated were Arbutus unedo, Calicotome villosa, Erica arborea, Myrtus communis, Phillyrea angustifolia, Pistacia lentiscus and Quercus suber. Species varied widely in crude protein content (55–221 g/kg DM), condensed tannins (1–360 g/kg DM), digestible dry matter (DM) (523–681 g/kg DM), asymptotic gas production (187–343 ml/g DM) and fractional gas production rate (0.030–0.047 h−1 ). Based on their in vitro digestibility and fermentation kinetics, species could be clustered in two groups of fodder resources, one of medium-high digestibility including the species M. communis, C. villosa, Ph. angustifolia and A. unedo and another group of low digestibility comprising the species P. lentiscus, Q. suber and E. arborea. The in vitro digestibility and gas production parameters were negatively correlated with phenolic compounds, in particular condensed tannins, suggesting that these in vitro techniques can be appropriate for detecting the presence of anti-nutritional substances in shrubs
Keywords: Gas production; In vitro digestibility; Nutritive value; Shrubs; Tannins

Assessment of the digestibility of some Mediterranean shrubs by in vitro techniques - Ammar, H.; López, S.; González, J. S. (Animal Feed Science and Technology, 2005)
The nutritive value of some Mediterranean browse species collected in Tunisia was studied on the basis of their chemical composition, in vitro digestibility and fermentation kinetics (gas production technique). The browse species evaluated were Arbutus unedo, Calicotome villosa, Erica arborea, Myrtus communis, Phillyrea angustifolia, Pistacia lentiscus and Quercus suber. Species varied widely in crude protein content (55–221 g/kg DM), condensed tannins (1–360 g/kg DM), digestible dry matter (DM) (523–681 g/kg DM), asymptotic gas production (187–343 ml/g DM) and fractional gas production rate (0.030–0.047 h−1 ). Based on their in vitro digestibility and fermentation kinetics, species could be clustered in two groups of fodder resources, one of medium-high digestibility including the species M. communis, C. villosa, Ph. angustifolia and A. unedo and another group of low digestibility comprising the species P. lentiscus, Q. suber and E. arborea. The in vitro digestibility and gas production parameters were negatively correlated with phenolic compounds, in particular condensed tannins, suggesting that these in vitro techniques can be appropriate for detecting the presence of anti-nutritional substances in shrubs
Keywords: Gas production; In vitro digestibility; Nutritive value; Shrubs; Tannins

In vitro gas production and its relationship to in situ disappearance and chemical composition of some Mediterranean browse species - Gasmi-Boubaker, Aziza; Kayouli, C.; Buldgen, A. (Animal Feed Science and Technology, 2005)
In vitro gas production of seven species (i.e., Arbutus unedo, Calycotum villosa, Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber) that are widely browsed by goats were measured through 120 h and related to in situ dry matter disappearance (DMD) and chemical composition. Three goats fitted with ruminal cannulae were used for the in vitro and in situ studies. Browses varied in their crude protein (CP: 55–221 g/kg DM) and neutral detergent fibre (360–551 g/kg DM) contents. High levels of total condensed tannins (TCT) were observed in Pistacia lentiscus, and the lowest levels were in Calycotum villosa and Phillyrea angustifolia. The browses varied widely in potential (145.7–224.0 ml/g DM) and fractional rates (0.038–0.075/h) of gas production, and there were differences among species in DMD (P < 0.05). Gas production at 24 h was positively correlated (P < 0.05) with in situ DM disappearance and CP content, but negatively correlated (P < 0.05) to acid detergent lignin (ADL), free condensed tannins (FCT) and TCT contents. The fractional rate of fermentation (μ) was negatively related (P < 0.05) to FCT (r = −0.81) and TCT (r = −0.83), whereas DMD was only related to acid detergent fibre and ADL content. Results support combined use of gas production and in situ techniques to determine the nutritive value of feeds containing phenolic compounds.
Keywords: Gas production; In situ disappearance; Shrubs; Tannins

In vitro gas production and its relationship to in situ disappearance and chemical composition of some Mediterranean browse species - Gasmi-Boubaker, Aziza; Kayouli, C; Buldgen, A (Animal Feed Science and Technology, 2005)
In vitro gas production of seven species (i.e., Arbutus unedo, Calycotum villosa, Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber) that are widely browsed by goats were measured through 120 h and related to in situ dry matter disappearance (DMD) and chemical composition. Three goats fitted with ruminal cannulae were used for the in vitro and in situ studies. Browses varied in their crude protein (CP: 55–221 g/kg DM) and neutral detergent fibre (360–551 g/kg DM) contents. High levels of total condensed tannins (TCT) were observed in Pistacia lentiscus, and the lowest levels were in Calycotum villosa and Phillyrea angustifolia. The browses varied widely in potential (145.7–224.0 ml/g DM) and fractional rates (0.038–0.075/h) of gas production, and there were differences among species in DMD (P < 0.05). Gas production at 24 h was positively correlated (P < 0.05) with in situ DM disappearance and CP content, but negatively correlated (P < 0.05) to acid detergent lignin (ADL), free condensed tannins (FCT) and TCT contents. The fractional rate of fermentation (μ) was negatively related (P < 0.05) to FCT (r = −0.81) and TCT (r = −0.83), whereas DMD was only related to acid detergent fibre and ADL content. Results support combined use of gas production and in situ techniques to determine the nutritive value of feeds containing phenolic compounds.
Keywords: Gas production; In situ disappearance; Shrubs; Tannins

Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila (Journal of Agricultural and Food Chemistry, 2003)
The gastroprotective effects of 70% acetone extracts of Quercus suber and Quercus coccifera leaves and of tannins (pedunculagin, castalagin, phillyraeoidin A, and acutissimin B) purified from these extracts were examined in the mouse using the ethanol-induced gastric ulcer model. Both extracts (25, 50, and 100 mg/kg), given orally, prevented the formation of ethanol-induced lesions in the stomach. The percent protection varied between 68 and 91%. Purified tannins (50 mg/kg) were also effective in protecting the stomach against ethanol, and the percent protection varied from 66 to 83%. Castalagin was the most potent. Both extracts and all of the tannins tested (10, 25, and 50 ?g/mL) strongly inhibited (55?65%) the lipid peroxidation of rabbit brain homogenate. These results suggest that the gastroprotective effects of extracts of Q. suber and Q. coccifera leaves and the purified tannins in this experimental model are related to their anti-lipoperoxidant properties. Keywords: Experimental gastric ulcer; lipid peroxidation; medicinal plants; Quercus sp.; tannins; castalagin
From Duplicate 2 (Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila)
Keywords: Acetone; Animals; Biphenyl Compounds; castalagin; Catechols; Catechols: therapeutic use; Ethanol; Experimental gastric ulcer; Hydrolyzable Tannins; lipid peroxidation; Lipid Peroxidation: drug effects; Male; Medicinal plants; Mice; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: therapeutic use; Plant Leaves; Plant Leaves: chemistry; Quercus; Quercus sp.; Quercus: chemistry; Rabbits; Stomach Ulcer; Stomach Ulcer: chemically induced; Stomach Ulcer: prevention & control; Tannins; Tannins: pharmacology; Tannins: therapeutic use

Dimeric and Trimeric Hydrolyzable Tannins from Quercus coccifera and Quercus suber - Ito, Hideyuki; Yamaguchi, Koji; Kim, Tae-Hoon; Khennouf, Seddik; Gharzouli, Kamel; Yoshida, Takashi (Journal of Natural Products, 2002)
Three new hydrolyzable tannins, cocciferins D1 (1), D2 (2), and T1 (4), were isolated from the leaves of Quercus coccifera. Cocciferin D2 (2) and two additional new tannins, cocciferins D3 (3) and T2 (5), were also obtained from the leaves of Quercus suber. Their oligomeric structures were elucidated on the basis of spectroscopic methods and chemical evidence. Compounds 2, 3, and 5 were rare oligomers possessing glucose cores with both open-chain and pyranose forms.
doi: 10.1021/np010465i
Keywords: NMR; Quercus coccifera; Quercus suber; structure (voyant); Tannins

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential

Effect of polyethylene glycol on in vitro degradability of nitrogen and microbial protein synthesis from tannin-rich browse and herbaceous legumes - Getachew, G; Makkar, H P S; Becker, K (BRITISH JOURNAL OF NUTRITION, 2000)
Determination of microbial degradability of N is important in formulating a sound supplementation strategy for efficient utilisation of basal as well as supplementary diet components. In vitro degradability of N (IVDN) from tannin-containing browses (Acacia cyanophylla, Acacia albida, Acioa barteri and Quercus ilex) and two herbaceous legumes (Desmodium intortum andDesmodium uncinatum) was determined using the in vitro gas-production method coupled with NH3-N measurement in the presence and absence of a tannin-binding agent (polyethylene glycol (PEG), molecular mass 6000). Addition of PEG to tannin-containing feeds significantly (P < 0.05) increased in vitro gas and short-chain fatty acid (SCFA) production, and IVDN. The use of PEG as a tannin-binding agent increased IVDN from 28 to 59, 32 to 72, 19 to 40, 32 to 73, 40 to 80, and 26 to 77 % in A. cyanophylla, A. albida, A. barteri, D. intortum, D. uncinatum and Q. ilexrespectively. There was significant correlation between total phenolic compounds (total phenol, TP; total tannin, TT) in leguminous forages and percentage increase in IVDN on addition of PEG (P < 0.05; R-2 0.70 and 0.82 for TP and TT respectively). The difference in IVDN observed in the absence and presence of PEG indicates the amount of protein protected from degradation in the rumen by tannins. When measured after 24 h incubation, tannin-containing feeds incubated in absence of PEG resulted in higher microbial protein synthesis than in the presence of PEG. Addition of PEG significantly (P < 0.05) reduced the efficiency of microbial protein synthesis expressed as mu mol purine/mmol SCFA.
Keywords: microbial protein synthesis; Polyethylene glycol; protein degradability; Tannins

Effect of polyethylene glycol on in vitro degradability of nitrogen and microbial protein synthesis from tannin-rich browse and herbaceous legumes - Getachew, G.; Makkar, H. P. S.; Becker, K. (BRITISH JOURNAL OF NUTRITION, 2000)
Determination of microbial degradability of N is important in formulating a sound supplementation strategy for efficient utilisation of basal as well as supplementary diet components. In vitro degradability of N (IVDN) from tannin-containing browses (Acacia cyanophylla, Acacia albida, Acioa barteri and Quercus ilex) and two herbaceous legumes (Desmodium intortum andDesmodium uncinatum) was determined using the in vitro gas-production method coupled with NH3-N measurement in the presence and absence of a tannin-binding agent (polyethylene glycol (PEG), molecular mass 6000). Addition of PEG to tannin-containing feeds significantly (P < 0.05) increased in vitro gas and short-chain fatty acid (SCFA) production, and IVDN. The use of PEG as a tannin-binding agent increased IVDN from 28 to 59, 32 to 72, 19 to 40, 32 to 73, 40 to 80, and 26 to 77 % in A. cyanophylla, A. albida, A. barteri, D. intortum, D. uncinatum and Q. ilexrespectively. There was significant correlation between total phenolic compounds (total phenol, TP; total tannin, TT) in leguminous forages and percentage increase in IVDN on addition of PEG (P < 0.05; R-2 0.70 and 0.82 for TP and TT respectively). The difference in IVDN observed in the absence and presence of PEG indicates the amount of protein protected from degradation in the rumen by tannins. When measured after 24 h incubation, tannin-containing feeds incubated in absence of PEG resulted in higher microbial protein synthesis than in the presence of PEG. Addition of PEG significantly (P < 0.05) reduced the efficiency of microbial protein synthesis expressed as mu mol purine/mmol SCFA.
The following values have no corresponding Zotero field: pub-location: C/O PUBLISHING DIVISION, WALLINGFORD OX10 8DE, OXON, ENGLAND publisher: C A B INTERNATIONAL
Keywords: microbial protein synthesis; Polyethylene glycol; protein degradability; Tannins

Changes in Tannic Composition of Reproduction Cork Quercus suber throughout Industrial Processing - Cadahía, Estrella; Conde, Elvira; Fernández de Simón, Brígida; García-Vallejo, María Concepción (Journal of Agricultural and Food Chemistry, 1998)
Tannic composition was studied in reproduction cork samples from three different trees of Spanish Quercus suber and at different industrial processing stages. The ellagitannins, roburins A and E, grandinin, vescalagin, and castalagin, were identified and quantified by HPLC. Global evaluations of tannins were also carried out, using classical chemical methods. The group of hydrolyzable tannins was the most abundant in the tannic extract in all samples; among them, castalagin was the main component, followed by vescalagin, grandinin, roburin E, and, to a much lesser extent, roburin A. The changes in tannic composition throughout the industrial processing are mainly related to the boiling process and are more pronounced in total phenol and proanthocyanidin contents than in individual ellagitannins content. Vescalagin and roburins A and E were selected as those variables that provided the greatest discrimination among stages. Important differences in the ellagitannin contents were observed among the trees studied, all of the ellagitannins being discriminant variables in this case. Keywords: Quercus suber; cork; tannins; ellagitannins; proanthocyanidins; polyphenols; high-performance liquid chromatography
doi: 10.1021/jf9709360doi: 10.1021/jf9709360The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; ellagitannins; high performance liquid chromatography; polyphenols; proanthocyanidins; Quercus suber; Tannins

Changes in Tannic Composition of Reproduction Cork Quercus suber throughout Industrial Processing - Cadahía, Estrella; Conde, Elvira; Fernández de Simón, Brígida; García-Vallejo, María Concepción (Journal of Agricultural and Food Chemistry, 1998)
Tannic composition was studied in reproduction cork samples from three different trees of Spanish Quercus suber and at different industrial processing stages. The ellagitannins, roburins A and E, grandinin, vescalagin, and castalagin, were identified and quantified by HPLC. Global evaluations of tannins were also carried out, using classical chemical methods. The group of hydrolyzable tannins was the most abundant in the tannic extract in all samples; among them, castalagin was the main component, followed by vescalagin, grandinin, roburin E, and, to a much lesser extent, roburin A. The changes in tannic composition throughout the industrial processing are mainly related to the boiling process and are more pronounced in total phenol and proanthocyanidin contents than in individual ellagitannins content. Vescalagin and roburins A and E were selected as those variables that provided the greatest discrimination among stages. Important differences in the ellagitannin contents were observed among the trees studied, all of the ellagitannins being discriminant variables in this case. Keywords: Quercus suber; cork; tannins; ellagitannins; proanthocyanidins; polyphenols; high-performance liquid chromatography
doi: 10.1021/jf9709360
Keywords: Cork; ellagitannins; high performance liquid chromatography; polyphenols; proanthocyanidins; Quercus suber; Tannins

Polyphenolic Composition of Quercus suber Cork from Different Spanish Provenances - Conde, Elvira; Cadahía, Estrella; García-Vallejo, María Concepción; Fernández de Simón, Brígida (Journal of Agricultural and Food Chemistry, 1998)
Polyphenolic composition was studied by HPLC and classical chemical methods in reproduction cork of Quercus suber from different Spanish provenances. The low molecular weight polyphenols (gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferyl, and sinapic aldehydes; and aesculetin and scopoletin) and the ellagitannins (roburins A and E, grandinin, vescalagin, and castalagin) were identified and quantified. Ellagic acid was the main component in the ether soluble fraction, and the group of hydrolyzable tannins, and among them castalagin, was the most abundant in the tannic extract in all the samples. Although there was an important variability among provenances, no significant differences were found in the total tannin content and in the individual content of each ellagitannin. However, gallic and caffeic acids and protocatechuic aldehyde provided the greatest discrimination among provenances. Keywords: Quercus suber; cork; polyphenols; tannins; phenolic acids and aldehydes; coumarins; ellagitannins; high-performance liquid chromatography
doi: 10.1021/jf970863kdoi: 10.1021/jf970863kThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; coumarins; ellagitannins; high-performance liquid chromatography; phenolic acids and aldehydes; polyphenols; Quercus suber; Tannins

Polyphenolic Composition of Quercus suber Cork from Different Spanish Provenances - Conde, Elvira; Cadahía, Estrella; García-Vallejo, María Concepción; Fernández de Simón, Brígida (Journal of Agricultural and Food Chemistry, 1998)
Polyphenolic composition was studied by HPLC and classical chemical methods in reproduction cork of Quercus suber from different Spanish provenances. The low molecular weight polyphenols (gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferyl, and sinapic aldehydes; and aesculetin and scopoletin) and the ellagitannins (roburins A and E, grandinin, vescalagin, and castalagin) were identified and quantified. Ellagic acid was the main component in the ether soluble fraction, and the group of hydrolyzable tannins, and among them castalagin, was the most abundant in the tannic extract in all the samples. Although there was an important variability among provenances, no significant differences were found in the total tannin content and in the individual content of each ellagitannin. However, gallic and caffeic acids and protocatechuic aldehyde provided the greatest discrimination among provenances. Keywords: Quercus suber; cork; polyphenols; tannins; phenolic acids and aldehydes; coumarins; ellagitannins; high-performance liquid chromatography
doi: 10.1021/jf970863k
Keywords: Cork; coumarins; ellagitannins; high-performance liquid chromatography; phenolic acids and aldehydes; polyphenols; Quercus suber; Tannins

EFFECTS OF TANNIN COMPOUNDS ON 2 SPECIES OF COLLEMBOLA - POINSOTBALAGUER, N; RACON, L; SADAKA, N; LEPETIT, J (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1993)
The effects of condensed and hydrolysable tannin extracted from evergreen oak leaves (Quercus ilex L.) were tested on two species of Collembola. Concentrations lower than those present in the litter leaves were toxic to these insects. Detoxification by washing with rainwater and biodegradation of tannic compounds are necessary for litter decomposition, in which microarthropods participated, to occur.
Citation
Keywords: Collembola; evergreen oak; Tannins

TANNIN LEVELS IN LEAVES OF SOME OAK SPECIES AT DIFFERENT STAGES OF MATURITY - Makkar, H P S; DAWRA, R K; Singh, B (JOURNAL OF THE SCIENCE OF FOOD AND AGRICULTURE, 1991)
Total phenolics, condensed tannins, degree of polymerisation, protein precipitation capacity, protein precipitable phenolics and specific activity (protein bound per unit tannins) were determined in the leaves of four oak species at different stages of maturation (4 days old to 1 year old). The content of total extractable phenols was higher in younger leaves in Quercus ilex Linn, Quercus semecarpifolia Sm and Quercus serrata Roxb, whereas in Quercus glauca Thunb the content was higher in the mature leaves. In all species studied, condensed tannins increased with maturation. Protein precipitation capacity had a trend similar to that of total phenols. In Q serrate and Q semecarpifolia the apparent degree of polymerisation increased, and the content of protein precipitable phenolics and specific activity decreased as the leaves matured. The decrease in protein precipitation capacity with maturation in these two species may be explained by both the decrease in the content and the change in the nature of phenols capable of binding proteins. Protein precipitation capacity was not detectable in Q ilex leaves. Protein precipitation capacity in the mature leaves decreased in the order of Q serrata > Q semecarpifolia > Q glauca > Q ilex.
Keywords: CONDENSED TANNINS; Tannins; TOTAL PHENOLS